PELAKSANAAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 10 TAHUN 2017 MENGENAI FASILITAS PEJALAN KAKI DI KOTA PEKANBARU TAHUN 2018-2019 - Emilia Fransiska; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The provision of pedestrian facilities in the form of sidewalks is a form of providing basic services by the Government to the community as supporting life activities to provide a sense of safety, comfort and order in traffic on the road. Therefore, Pekanbaru City has provided sidewalks as infrastructure for pedestrians and has also been regulated in the Pekanbaru City Regional Regulation No. 10 of 2017 concerning Traffic and Road Management.The purpose of this study is to describe the implementation of Pekanbaru City Regional Regulation Number 10 of 2017 regarding pedestrian facilities in Pekanbaru City and then also to find out the factors that hinder the implementation of Pekanbaru City Regional Regulation Number 10 of 2017 concerning pedestrian facilities in Pekanbaru City. 2018-2019. The theory used in this research is the theory of policy implementation by George C. Edward III. This type of research is descriptive qualitative. The data collection technique is done by interview and documentation.The results of this study are the implementation of policies regarding pedestrian facilities in Pekanbaru City has not been implemented optimally. There are still sidewalks that are not well maintained and even those sidewalks are often misused by other parties. This is due to ineffective communication in terms of distribution, clarity of regulations and consistency. Then because of limited human and financial resources, the attitude of policy implementers who have not been firm in responding to this problem, the organizational structure does not have a clear SOP and no sanctions have been set in the policy.   Keywords: Policy Implementation, Sidewalks, Pedestrians